Relevance of Islamic Financial Instruments in Financing Micro and Small Enterprises in Gombe State, Nigeria - Hamza Abubakar Hussaini; Yakubu Tahir Maigari; Adamu Abubakar Muhammad (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
This paper aimed to investigate the role of Islamic financial instruments in providing financial support to micro and small enterprises in Nigeria at large and Gombe state in particular. Despite the opportunities presented by the micro and small enterprise sector for economic growth and investment as well as job opportunities, the sector is largely underdeveloped due to lack of direct access to capital and poor managerial experience by many entrepreneurs. This research paper uses a unique combination of qualitative and quantitative research methods to understand the existing financing structures, challenges and identify the potential of Islamic financial instruments as a source of capital for micro and small enterprises in Gombe state Nigeria. The research adopts a series of semi-structured interviews, document analysis, and a survey of various micro and small enterprises within Kashere town and Gombe metropolis for sampling. The findings of the research suggest that the majority of micro and small enterprises are unaware of or having no access to Islamic financial instruments for funding businesses and there is need for better education and awareness regarding these instruments. Additionally, the research paper concludes with recommendations for policymakers, institutions and practitioners on how to increase the use of Islamic financial instruments in Gombe state Nigeria and proper awareness to promote micro and small enterprises for economic growth and development within the study area. Keywords: Islamic Financial Instruments, Micro-Enterprises, Nigeria